Imagining Futures: Theorizing the Practical Knowledge of Future-making. Issue 2 (February 2022) - Thompson, Neil Aaron; Byrne, Orla
The study of future-making – how practitioners make and enact imagined futures – has become a cornerstone for understanding the temporal dynamics of organization, strategy and entrepreneurship. This article investigates the texture of practical knowledge that enables entrepreneuring practitioners to jointly address the challenges inherent to future-making. We conduct a video ethnography of a business modelling programme producing 79 hours of audio-visual recordings. Using multimodal conversation analysis, we unpack different forms of practical knowledge that simultaneously binds practitioners in a web of mutual expectations and establishes modes of thinking and acting for the creation of imagined futures. This contributes to existing studies by demonstrating that the discursive, embodied and material dimensions of future-making are fundamentally entangled within textures of practical knowledge. Consequently, we shift the mode of theorizing towards non-representationalism, which opens up new frontiers for future research to observe, participate and reflect with practitioners on the textures of practical knowledge constitutive of future-making in different circumstances and contexts.